CORPUS USED AS A DATA-DRIVEN LEARNING TOOL IN L2 ACADEMIC WRITING: EVIDENCE FROM TURKISH CONTEXTS - Emir, Gamze; Yangın Ekşi, Gonca (TEFLIN Journal, 2023)
This study investigated the effectiveness of using corpus as a data-driven learning (DDL) tool to enhance the academic writing skills of Turkish EFL learners. The study also explored learners’ views of the potential use of corpus in L2 academic writing. To achieve these objectives, a mixed-method sequential explanatory design was employed, involving freshman student teachers enrolled in the Department of English Language Teaching at a state university in Turkey. The participants completed four argumentative essay writing tasks. Two tasks employed conventional techniques for error correction, while the other two utilized corpus as a reference tool for error correction. The latter two tasks were complemented by corpus training for the participants. The results indicated that using corpus as a DDL tool had a significant impact on the academic writing skills of Turkish EFL learners, with notable improvements observed in both grammar and vocabulary use. Participants also expressed positive feedback on the use of corpus as a DDL tool in enhancing their L2 academic writing.